Treatment of central giant cell lesions using bisphosphonates with intralesional corticosteroid injections - da Silva, Newton Guerreiro (BioMed Central, 2012)
Central giant cell lesions are benign intraosseous proliferative lesions that have considerable local aggressiveness. Nonsurgical treatment methods, such as intralesional corticosteroid injections, systemic calcitonin and interferon have been reported. Recently, bisphosphonates have been used to treat central giant cell lesions. A case of a 36-year-old male with a central giant cell lesion crossing the mandibular midline was treated with intralesional corticosteroids combined with alendronate sodium for the control of systemic bone resorption. The steroid injections and the use of bisphosphonates were stopped after seven months when further needle penetration into the lesion was not possible due to new bone formation. After two years, the bony architecture was near normal, and only minimal radiolucency was present around the root apices of the involved teeth. The patient was followed up for four years, and panoramic radiography showed areas of new bone formation. Thus far, neither recurrence nor side effects of the medication have been detected.